Ayurvedic plumbism. Issue 7 (July 2017) - Sadler, Matthew; Bell, Sarah
Abstract: Ayurveda is a traditional medicine native to India but is used in many parts of the world as an alternative or adjunct to standard medicine. Preparation can involve incorporation of heavy metals, including lead. We report the case of a 64‐year‐old man presenting with malaise, abdominal pain, anaemia and very high lead levels. He was found to be taking ayurvedic medicines to help his diabetic control. Analysis of the ayurvedic medications showed several with very high lead content. Following treatment with an oral chelating agent, the patient's symptoms and blood abnormalities resolved. This case highlights the need to be aware of potentially toxic alternative medications patients take and the efficacy of oral treatment choices in lead poisoning.